Endothelial Metabolism Driving Angiogenesis. Issue 4 (July 2015) - Cantelmo, Anna Rita; Brajic, Aleksandra; Carmeliet, Peter
<x xml:space="preserve">Abstract</x> Abstract Angiogenesis has been traditionally studied by focusing on growth factors and other proangiogenic signals, but endothelial cell (EC) metabolism has not received much attention. Nonetheless, glycolysis, one of the major metabolic pathways that converts glucose to pyruvate, is required for the phenotypic switch from quiescent to angiogenic ECs. During vessel sprouting, the glycolytic activator PFKFB3 (6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase-3) promotes vessel branching by rendering ECs more competitive to reach the tip of the vessel sprout, whereas fatty acid oxidation selectively regulates proliferation of endothelial stalk cells. These studies show that metabolic pathways in ECs regulate vessel sprouting, more importantly than anticipated. This review discusses the recently discovered role of glycolysis and fatty acid oxidation in vessel sprouting. We also highlight how metabolites can influence EC behavior as signaling molecules by modulating posttranslational modification.